2019
DOI: 10.1002/hbm.24506
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the neural correlates of doorway freezing in Parkinson's disease

Abstract: Freezing of gait (FOG) in Parkinson's disease (PD) is frequently triggered upon passing through narrow spaces such as doorways. However, despite being common the neural mechanisms underlying this phenomenon are poorly understood. In our study, 19 patients who routinely experience FOG performed a previously validated virtual reality (VR) gait paradigm where they used foot‐pedals to navigate a series of doorways. Patients underwent testing randomised between both their “ON” and “OFF” medication states. Task perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 64 publications
4
49
0
Order By: Relevance
“…The origin of these dysfunctional dynamics is unclear. One possibility is that the deficient cortical-subcortical communication in gait freezing relies on a defective engagement of the SMA (Hanakawa et al , 1999; Iseki et al , 2010; Tard et al , 2015; Matar et al , 2018, 2019) in the context of basal ganglia pathology (de Hemptinne et al , 2013; Brittain and Brown, 2014; Lewis and Shine, 2016). Indeed, the cortical-subthalamic decoupling was limited to the hemisphere with greater dopaminergic denervation in a context of unbalanced dopaminergic loss between the two hemispheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of these dysfunctional dynamics is unclear. One possibility is that the deficient cortical-subcortical communication in gait freezing relies on a defective engagement of the SMA (Hanakawa et al , 1999; Iseki et al , 2010; Tard et al , 2015; Matar et al , 2018, 2019) in the context of basal ganglia pathology (de Hemptinne et al , 2013; Brittain and Brown, 2014; Lewis and Shine, 2016). Indeed, the cortical-subthalamic decoupling was limited to the hemisphere with greater dopaminergic denervation in a context of unbalanced dopaminergic loss between the two hemispheres.…”
Section: Discussionmentioning
confidence: 99%
“…and leading to unsuccessful attempts at forward stepping (Schlenstedt et al , 2018). Recent findings with functional MRI have revealed that doorway-provoked gait freezing (in virtual reality) was associated with selective hypoactivation of the (pre)SMA (Matar et al , 2018, 2019). In this study, the authors also showed a cortical-subthalamic decoupling during gait freezing thus further supporting our real-life results (Matar et al , 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Aron et al, 2007;Aron and Poldrack, 2006;Jahfari et al, 2011;Rae et al, 2015). Further, efficiency of inhibitory control is dependent on the strength of fronto-basal ganglia connectivity (Chavan et al, 2017;Forstmann et al, 2012;Jahfari et al, 2012;Matar et al, 2019). Motor output through the thalamus (THAL) is thought to be under the direction of signals originating from frontal regions via three pathways through the basal ganglia; the direct, indirect and hyperdirect pathways (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A complicating factor is that a validated paradigm to study visually cued lower limb movement (as a proxy for gait) in a neuroimaging study is not yet available. Unfortunately, our attempt to extend an established virtual environment paradigm (54,55,57,(71)(72)(73)(74)(75) by incorporating visual cues did not result in a validated paradigm for future use in neuroimaging studies and behavioural studies on visual cueing in persons with PD and FOG (Chapter 10). As discussed elaborately in the Discussion section of Chapter 10, the visual cues in the virtual environment apparently 'did not have what it takes' to improve movement control.…”
Section: Development Of Novel Cueing Strategiesmentioning
confidence: 99%
“…However, improvements to the paradigm, such as strengthening the coupling between foot movements and the view in the virtual environment, could render the paradigm better suited for the purpose of studying the neurophysiology of cueing. Considering the value that the virtual environment paradigm has had in the study of the pathophysiology of FOG (54,55,57,(71)(72)(73)(74)(75), this paradigm, if adjusted, does hold potential to study the neurophysiological grounds of visual cueing.…”
Section: Development Of Novel Cueing Strategiesmentioning
confidence: 99%